Działania 2 Poznańskiego Oddziału Wojsk Ochrony Pogranicza przeciwko grupom zbrojnym na terenie pogranicza - Michał Trojanowski (In Gremium. Studies in History, Culture and Politics, 2016)
Operations of 2nd Poznań Border Guard Forces (pl. Wojska OchronyPogranicza) against armed groups in the border areaThis formation was participating in consolidation of the political system imposed by Moscow. It secured public order and organized armed operations within the area of its jurisdiction i.e. Krosno, Słubice and Gubin County, against armed groups. During these operations, it mainly encountered militias of criminal nature. In the responsibility sector of members of the Krosno Border Guard Forces, there were no activities noted with participation of armed groups belonging to the independence  underground. In the period, when the Maneuver Task Force of the Division was involved in the fight against Ukrainian Insurgent Army in Bieszczady Mountains during Wisła Action (pl. Akcja Wisła), this unit has issuedimprovised emergency subdivisions. The formation in its operations cooperated with field stations of Citizen’s Militia (pl. Milicja Obywatelska) and Security Service (pl. Służba Bezpieczeństwa).